Genetic and Epigenetic Resistance of SL/Ni Mice to Lymphomas - Shisa, Hayase (Jpn J Cancer Res, 1996)
The murine spontaneous B lymphoma is etiologically related to the expression of endogenous ecotropic marine leukemia virus (ETV). Although both SL/Kh and SL/Ni mouse strains show a high level of expression of ETV from early in life, the former is a pre‐B lymphoma‐prone strain and the latter is rather lymphoma‐resistant. In order to identify the host background difference related to the lymphomagenesis, we performed a genetic cross study between these two strains. In the reciprocal F(1) generation, the length of the lymphoma latent period was slightly but significantly longer in (SL/Ni XSL/Kh)F(1) than in (SL/Kh × SL/Ni)F(1) (P<0.05). The incidence of overall lymphomas and that of acute pre‐B lymphomas was lower in (SL/Ni × SL/Kh)F(1) than in (SL/Kh × SL/Ni)F(1), although the difference was not statistically significant. These observations indicate that an epigenetic maternal resistance mechanism of SL/Ni mice plays a role in the lymphoma resistance. Furthermore, in the backcross combinations without maternal influence of SL/Ni, we observed a genetic mechanism of lymphoma resistance: an SL/Ni‐derived recessive lymphoma‐resistance gene mapped in the proximal segment of Chr. 4. We named this gene nir‐1 (SL/Ni‐lymphoma resistance‐1). Thus, we have demonstrated epigenetic and genetic mechanisms of lymphoma resistance of the SL/Ni mouse with the high expression of endogenous ETV.